A theological appraisal of the satisfaction theory of atonement : Implications for the Ghanaian context - Boaheng, Isaac (Stellenbosch Theological Journal, 2024)
The doctrine of atonement is central to the logic of the Christian faith. As a core part of Christian theology, the subject of atonement has received much scholarly attention since the emergence of the Christian church. Different scholars have interpreted Christ’s atoning sacrifice in different ways based on their socio-political milieu. One of such interpretations is Anselm’s satisfaction theory which considers the atonement as a supererogatory act that provided satisfaction for humankind’s disobedience of God. Like any other model of atonement, Anselm’s model has its strengths and limitations. The lack of literature on the contextual application of Anselm’s satisfaction theory to the Ghanaian context has prompted this study which appraises the theory and then discusses how it might address selected challenges facing the contemporary Ghanaian society. The methodology used for the first task comprised a synchronic historical review and conceptual analysis of existing literature on the satisfaction theory. Among other things, the study found that the satisfaction theory rightly considers God as the receiver of the atonement but fails to address pertinent issues regarding God’s redemptive and covenantal nature. This was followed by a comparative study between Anselm’s socioeconomic and political contexts and those of contemporary Ghana. Based on this, contextual applications of the theory were deduced for contemporary Ghana. The article contributes to the contemporary Christian discourse on the doctrine of soteriology and its relevance for the human society.